The Effectiveness of Program based on Strengthening Self-Concept using Braille sense Technology in Improving the Adjustment Behavior and Achievement among Blind Inclusive 1st Year Secondary School students - Moustafa, Ashraf Mohamed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effectiveness of a program based on strengthening self-concept using Braille Sense technology in improving the adjustment behavior and academic achievement of blind students integrated in the first grade of secondary school. The quasi-experimental approach was adopted and the study tools consisted of the Self-Concept Scale for the Blind and the adjustment Behavior Scale for the Blind, As well as the training program, the study tools were applied to a sample of (32) blind students in the first grade of secondary school in the United Arab Emirates, as a pre-measurement, and the sample was divided based on the calculation of the fourths, where the first quadrant represents eight blind low-grade students in self-concept and consensual behavior based on that Qualitative analysis that shows the difference in dimensions in terms of decrease and height on the self-concept scale, so that the first quadrant group (8) represents blind students who are the exploratory sample through which the validity of the study hypotheses will be verified.. The results of the study showed the following, the existence of statistically significant differences between the performance of the intervention group in the pre-, post- and tracer measurements in terms of adjustment behavior and its various dimensions in favor of the post-measurement, and the existence of statistically significant differences between the performance of the intervention group in the pre-, post- and tracer-measurements in terms of academic achievement in favor of the post-measurement.